2020
DOI: 10.15587/1729-4061.2020.206395
|View full text |Cite
|
Sign up to set email alerts
|

Investigating an alternative electricity supply system for preventing emergencies under conditions of limited capacity

Abstract: and catastrophes of various nature including those of medical and biological character (COVID 19). Their complexity and complicated socio-economic implications actualize the issue of readiness of governance bodies, as well as their capa-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The samples obtained showed an efficiency of less than 10 %. The authors of [17] demonstrated the creation of tandem structures, but despite the prospects in this direction, the efficiency of the developed device structures did not exceed 14 %. Another important procedure that causes discussion is the chemical treatment and annealing of the device structure after the deposition of the base layer [18].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The samples obtained showed an efficiency of less than 10 %. The authors of [17] demonstrated the creation of tandem structures, but despite the prospects in this direction, the efficiency of the developed device structures did not exceed 14 %. Another important procedure that causes discussion is the chemical treatment and annealing of the device structure after the deposition of the base layer [18].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%